Analysis of users' searches of CD-ROM databases (2005)
Purpose- This study investigates the behaviour of searches of CD-ROM databases in the Kenneth Dike library of the university of Ibadan, Nigeria. The aim of the study was to identify the behaviour of end-users with different amounts of overall experience in searching electronic databases in order to identify the knowledge of thier search systems and syntax, and its effect on thier search result, for the purpose of improving user education. Design/methodology/approach-All end-user who conducted searches during the priod of the research were the subject of the research. A well-constructed questionnaire, including interveiws and observations, were used to collect the requisite data. The variables included in this study are uservariables, search process variables and search outcome variables. Data were analyzed using descriptive statistics. Finding- The results show that logical operates "AND" and "OR" are significantly used for searching by end-users; that search results are dependent on search strategy employed by the user. The more sophisticated the search strategy, the greater the result in term s of number and revelance obtained by the searcher. The result also shows that there is no relationship between the level of education of users and quality of search strategy. Practical implications- The implication of study is mainly the importance and necessity of training for end-users in CD-ROM literature search. Originality/ value- The uniqueness of the study is based on the fact that certain strategic methods are required for successful CD_ROM literature search and that this does not depend on the level of education of users. This paper is therefore important and applicable to all end-users who are interested in conduction CD_ROM literature search.